India's economic reforms; Steps ahead - Bajpai, Nirupam (New Delhi, 1996)
In this paper we suggest further steps that India needs to take in the process of her economic reforms. While the reform measures undertaken during 1991-96 have led to considerable deregulation and liberalization of the Indian economy, a lot still remains on India's unfinished reform agenda. The experience of East Asian countries along with that of China is taken into account in suggesting relevant lessons for the future course of India's economic reforms. Among other things, we highlight the need for much greater openness of the economy, deregulation of the private sector, exit policy, and reform of the labor and land laws. Besides, in our view, the government needs to focus its attention to and provide larger resources for primary health and primary education. The main quantitative conclusion is that India can expect per capita economic growth of a mere 3.5 percent per year under current policies, but could raise the overall per capita growth rate to as much as 7 percent per year under extensive market reforms that delivered a national saving rate and efficient market institutions similar to those of East Asia.
Keywords: Economic reforms - India